Additional records of Norwegian skate Dipturus nidarosiensis (Storm, 1881) (Pisces: Rajidae) in the Adriatic Sea - Isajlović, Igor (Array, 2020)
Additional records of the Norwegian skate Dipturus nidarosiensis (Storm, 1881)from the Adri-atic Sea are reported. Two specimens were collected in the southern Adriatic Pit in 2008 and 2010, respectively. The records reported herein improve our knowledge on the distribution of a rarely encountered, deep water species D. nidarosiensis, whose presence has only recently been confirmed in the Mediterranean Sea.